Analysis of Buying and Selling Fish Through Auctions Perspective of Sharia Economic Law: Case Study of TPI Kota Agung Tanggamus - Nafisah, Jauharotun; Irhamudin; Ismanto, Bambang (Journal Tafkirul Iqtishodiyyah, 2021)
Buying and selling is a form of exchange of goods or currency in one place. It is inseparable from the sale and purchase carried out by coastal communities at the auction place for fish buying and selling transactions. The sale and purchase is an auction. How to study or analyze the concept of buying and selling in sharia auctions or sharia economic law studies. This will be the focus of this research. This type of research is a field qualitative research and this research uses a qualitative descriptive research approach. Sources of data used are primary and secondary data sources. Data collection techniques using observation, interviews and documentation with data triangulation method. The results showed that the fish auction system at TPI Kota Agung Tanggamus in terms of the perspective of Sharia Economic Law did not meet Islamic sharia principles which were very concerned about the Pillars and Conditions in muamalah, where in this TPI in the process the fish being auctioned did not go through the process of weighing first so that the absence of clear details regarding the weight of the fish to be auctioned, the buyer can only estimate how much the weight of the fish he will buy will make it easy for bidders to suffer losses if they miscalculate. This is clearly the case that one of the conditions for the goods being auctioned is not fulfilled where the goods being auctioned must be far from the element of uncertainty (ghoror).